Ventral C1 Fracture Combined with Congenital Posterior Cleft: What to Do? - Gembruch, Oliver; Dammann, Philipp; Schoemberg, Tobias; Ahmadipour, Yahya; Payer, Michael; Sure, Ulrich; Tessitore, Enrico; Özkan, Neriman (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Objective We present a treatment approach for a rare condition of patients with a ventral C1 fracture and a congenital cleft in the posterior arch (half-ring Jefferson fracture) with an intact transverse atlantal ligament. Our technique aims to achieve stability of the atlanto-occipital and atlantoaxial joints while preserving mobility of the upper cervical spine.Patients and Methods Two male patients, 43 years and 29 years of age, respectively, were admitted to our hospital due to a fracture of the ventral arch of the atlas with no damage of the transverse atlantal ligament. Both men also presented a congenital cleft of the posterior arch. Initial conservative management with a halo-thoracic vest was performed in one case and failed. As a result, surgical treatment was performed in both cases using bilateral C1 mass screws and a transverse connector.Results The patients showed no neurologic deficits on follow-up examination 4 weeks after surgery with a full range of head and neck motion. Computed tomography (CT) showed no dislocation of the implanted material with good dorsal alignment and a stable ventral fracture distance. Follow-up CT showed osseous stability in both cases with the beginning of bony ossification of the bone graft.Conclusion Isolated instable fractures of the ventral arch of the atlas with a congenital cleft of the posterior arch with no damage of the transverse atlantal ligament can be stabilized using bilateral C1 mass screws and a transverse connector preserving upper cervical spine mobility.
Keywords: cervical spine; atlas fracture; congenital cleft; atlantoaxial instability; cervical anomalies